A shift-add algorithm for generating B-spline - GU, Feng (Computer Assisted Methods in Engineering and Science, 2017)
A CORDIC- based shift-add algorithm for generating B-spline curves is presented in this paper. This algorithm can be realized by hardware without multiplier, or coded with assembly language and run in the basic computing system which exists in many application systems. Convergence of the algorithm was proved. Errors were estimated and well controlled in the algorithm. A numerical experiment was carried out to validate algorithm. This algorithm can be used for adding complex curve plotting functions in embedded systems.